Optimizing Tomato (Solanum lycopersicum L.) Growth With Different Combinations of Organo-Mineral Fertilizers - Traoré, Adama; Bandaogo, Alimata Arzouma; Savadogo, Ouango Maurice; Saba, Fatimata; Ouédraogo, Audrey Leiticia; Sako, Yaya; Sermé, Idriss; Ouédraogo, Souleymane (Frontiers in Sustainable Food Systems, 2022)
With the aim of promoting sustainable agriculture that respects the environment and human health, a study was carried out to evaluate the impact of organic and mineral fertilizers on tomato plant cultivation. The study was carried out at the research station of Farako-Bâ in Burkina Faso on the Mongal F1 hybrid tomato variety. A complete randomized blocks of Fisher design with four replications was used to carried out the experiment. The treatments were: T0: control (compost15 t/ha) T1: compost (15 t/ha) + biosol (160 kg/ha) + urea (35 kg/ha) +NPK (87,5 kg/ha) + KCl (52,5 kg/ha) T2: compost (15 t/ha) + Neem seed cake (10 t/ha) + Urea (100 kg/ha) +NPK (250 kg/ha) + KCl (150 kg/ha) T3: compost (15 t/ha) + biochar (10 t/ha) + Urea (100 kg/ha) +NPK (250 kg/ha) + KCl (150 kg/ha). The data collected were collar diameter, height of plants, number of fruits, fruit diameter and tomato fruits yield. The results showed that the combination organo-mineral fertilizers had significant effect on tomato plant productivity. Application of neem seed cake and mineral fertilizer was the most efficient treatment with a yield increase of 53% and 40% over in 2019, respectively. In 2020, the yield increase was 32% and 85% biochar and biosol. Incorporation of organo-mineral fertilizers has improved soil organic and nutrients status which ultimately promote crop growth of tomato plant.